The Pro Allele of the p53 Codon 72 Polymorphism Is Associated with Decreased Intratumoral Expression of BAX and p21, and Increased Breast Cancer Risk - Proestling, Katharina; Hebar, Alexandra; Pruckner, Nina; Marton, Erika; Vinatzer, Ursula; Schreiber, Martin (PLOS ONE, 2012)
Background The TP53 Arg72Pro polymorphism encodes two p53 variants with different biochemical properties. Here we investigated the impact of this polymorphism on the expression of key p53 target genes in a panel of human breast carcinomas, breast cancer risk, and age at onset. Methodology/Principal Findings The Arg72Pro polymorphism was genotyped in 270 breast cancer patients and 221 control subjects. In addition, the Arg72Pro genotype of 116 breast tumors was determined, and correlated with intratumoral mRNA expression of TP53 and its key target genes MDM2, p21, BAX, and PERP, as quantified by qRT-PCR. We found a significantly increased breast cancer risk associated with the Pro-allele (per-allele odds ratio, 1.46; 95% confidence interval, 1.08–1.99), and a significantly later mean age at breast cancer onset for Pro/Pro patients (63.2±18 years) compared to Arg/Arg patients (58.2±15 years). The frequency of somatic TP53 inactivation was 25.4% in Arg/Arg, 20.9% in Arg/Pro, and 16.7% in Pro/Pro patients, which may reflect a higher selective pressure to mutate the Arg-allele. The median mRNA levels of p21 and BAX in the tumors of Pro-allele carriers were significantly reduced to 55.7% and 76.9% compared to Arg/Arg patients, whereas p53, MDM2 and PERP expression were hardly altered. Conclusions/Significance The p5372Arg variant appears to be a more potent in vivo transcription factor and tumor suppressor in human breast cancer than the p5372Pro variant. The Arg72Pro genotype has no significant effects in patients with TP53 mutated tumors, in which p53 is non-functional.